Comparative study of the electronic structure of CO, CO + K, NO and NO + K on Ni (111) by ARUPS using synchrotron radiation - Schneider, C.; Steinrück, Hans-Peter; Pache, T.; Heimann, P.A.; Coulman, D.; Umbach, E.; Menzel, Dietrich (Vacuum, 1990)
Using angle-resolved UV photoemission spectroscopy (ARUPS) with linerly polarized synchrotron radiation, the authors have studied the electronic structure, 2D band structure and orientation, and the energy dependence of the photoionization cross-sections of the valence levels for various pure and coadsorbed layers of CO and NO on Ni(111). This report summarizes and compares the results of these investigations. It is shown that the position of the shape resonance in the valence spectra cannot be taken as a measure for the intermolecular bonding distance.